Problematika Pengelolaan Tanah Wakaf di Desa Entak - Khabib Muhammad Al Barokah; Ma’rufi, Anwar; Abqori, Najih (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Waqf is a vital instrument in Islamic socio-religious development. However, its management at the village level faces significant challenges, as seen in Entak Village, Ambal Subdistrict, Kebumen Regency. This study aims to identify the main problems in waqf land management in the village and to formulate strategic solutions for improving local waqf governance. Using a qualitative case study approach, the research involved field observation, interviews with nadzir (waqf managers), and document analysis. The findings reveal three major challenges: weak capacity of nadzir in asset management, lack of formal legal status for waqf lands, and low community awareness about waqf principles and laws. As a result, many waqf assets remain underutilized or are at risk of disputes. To address these issues, the study recommends capacity-building programs for nadzir, accelerated land certification through collaboration with BPN and BWI, and community-based public education. These strategies are expected to promote more professional, productive, and sustainable waqf management at the grassroots level.